2017
DOI: 10.1161/circulationaha.116.025164
|View full text |Cite
|
Sign up to set email alerts
|

Lower Circulating Folate Induced by a Fidgetin Intronic Variant Is Associated With Reduced Congenital Heart Disease Susceptibility

Abstract: We report a previously undocumented finding that decreased circulating folate levels induced by increased folate transmembrane transport and utilization, as determined by the intronic variant, serves as a protective mechanism against CHD. Our results may explain why circulating folate levels do not have a good diagnostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…It is not surprising that such variants have only moderate contribution to risk and progression of cancers, if any, particularly compared to germline mutations that are associated with some distinct disease phenotypes. This is particularly true for a single locus change such as the MTOR rs2536 T > C change, which is similar to other functional studies focused on single germline variant . The effect of such germline variants on gene expression is also likely to be affected by other molecular events that govern gene expression regulation, such as long coding RNAs and circular RNAs that are competing endogenous RNAs (ceRNAs), which may disrupt the binding of miRNA to 3′UTR of the genes.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is not surprising that such variants have only moderate contribution to risk and progression of cancers, if any, particularly compared to germline mutations that are associated with some distinct disease phenotypes. This is particularly true for a single locus change such as the MTOR rs2536 T > C change, which is similar to other functional studies focused on single germline variant . The effect of such germline variants on gene expression is also likely to be affected by other molecular events that govern gene expression regulation, such as long coding RNAs and circular RNAs that are competing endogenous RNAs (ceRNAs), which may disrupt the binding of miRNA to 3′UTR of the genes.…”
Section: Discussionmentioning
confidence: 53%
“…This is particularly true for a single locus change such as the MTOR rs2536 T > C change, which is similar to other functional studies focused on single germline variant. [43][44][45] The effect of such germline variants on gene expression is also likely to be affected by other molecular events that govern gene expression regulation, such as long coding RNAs and circular RNAs that are competing endogenous RNAs (ceRNAs), 46,47 which may disrupt the binding of miRNA to 3 0 UTR of the genes. This might be the reason for the relatively less strong impact of miRNA-150 on modulating the MTOR expression associated with the MTOR rs2536 T > C change.…”
Section: Discussionmentioning
confidence: 99%
“…The same study observed that the depletion of FIGN resulted in alterations in the structure of mitotic centrosomes. However, Wang et al 49 have recently identified a FIGN intronic variant (rs2119289) that has a protective role against congenital heart disease. This finding is compatible with the role of FIGN as contributing to modulating HPAH penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…FIGN 491 encodes fidgetin, a microtubule-severing enzyme most highly expressed in the pituitary 492 gland and ovary (50). A genetic variant in FIGN was found to reduce the risk of congenital 493 heart disease in Han Chinese by modulating transmembrane folate transport (67,68). The 494 TAD encompassing the association signal in this locus includes FIGN and extends upstream 495 to the GRB14 gene (Fig 9).…”
Section: Subtypes In Pcos Families 398mentioning
confidence: 99%